A Method for Temporally Resolved Continuous Inline Measurement of Multiple Solute Concentrations With Microfluidic Spectroscopy - Andrea Lorenzo Henri Sergio Detry; Vinny Chandran Suja; Nathaniel Merriman Sims; Robert A. Peterfreund; David E. Arney (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: To develop a compact, real-time microfluidic spectroscopy system capable of simultaneously measuring the concentrations of multiple solutes flowing together through a single fluid pathway with high temporal resolution. Methods: The measurement system integrates a Z-flow cell and dual-wavelength LED light sources with a compact spectrophotometer. The experimental setup consisted of two clinical infusion pumps delivering distinct marker dyes through a common fluid pathway composed of a clinical manifold and a single lumen of a clinical intravascular catheter, while a third pump delivered an inert carrier fluid. Concentration measurements of the mixed dyes were performed at high-frequency sampling intervals, with dynamic pump rate adjustments to evaluate the system's ability to detect real-time changes in solute concentration. A MATLAB-based control application enabled automated data acquisition, processing, and system control to enhance experimental efficiency. Results: The system accurately measured solute concentrations, capturing temporal variations with high precision. It demonstrated high reproducibility with a standard error of the mean no larger than $0.19 \,μ g/mL$ for Erioglaucine and $1.32 \,μ g/mL$ for Tartrazine at steady state, and high accuracy with a maximum deviation of $0.21 \,μ g/mL$ for Erioglaucine and $0.5 \,μ g/mL$ for Tartrazine from the expected steady-state concentrations. Conclusions: This system enables continuous, real-time monitoring of multiple solutes in dynamic flow conditions, offering a portable solution with high sensitivity to temporal concentration changes—advancing beyond traditional static fluid measurement methods.